Impact of waqf financing on Federal government expenditure and debt in Malaysia / Azniza Hartini Azrai Azaimi Ambrose - Azniza Hartini, Azrai Azaimi Ambrose (2018)
Waqf was the provider of public goods, mixed public goods, and social services in Islamic history. In present economies, the goods and social services are provided by the government instead. These and other government expenditure components have caused burgeoning expenditure and excessive debt. In the case of Malaysia, the federal government has introduced the goods and services tax (GST) and reduced federal government expenditure to mitigate these issues. However, this strategy combination could cost welfare greatly. As such, this thesis aims to propose waqf as a means to finance certain Malaysian federal government expenditure and analyse its impact on federal government debt. To achieve this aim, mixed methods research was employed. For the qualitative part, primary data were collected through semi structured interviews with waqf experts consisting of academicians, government officials, and industry players. Thematic analysis and interpretive method of analysis were then perform to identify the viability of the proposal, to come out with a model, and to investigate the resultant impact of this particular waqf implementation on federal government debt. In addition, input on the form of waqf capital and method to safeguard its perpetuity were also obtained from the mentioned methods of analyses to complete the theoretical model. The completed theoretical model forms a dynamic stochastic general equilibrium (DSGE) model for the quantitative part. Data for the quantitative part was gathered from the literature, the Central Bank of Malaysia (BNM), and Public Mutual Berhad. These data helped determine the parameter values and some steady state values using ordinary least squares (OLS) method. Other steady state values were derived from the stationarised model equilibrium. To investigate the resultant impact of waqf on federal government debt, the model equilibrium were subjected to simulation analysis. The qualitative part of this thesis reveals that waqf financing certain federal government expenditure is doable because of political will, Shari’ah permissibility, and evidence of its implementation in the past. However, the application will not be without legal, management, financial, and public perception issues. Through partial centralisation of waqf laws, publication of waqf reports, revival of waqf deeds, human resource empowerment, and innovative waqf investment, those issues can be mitigated and model for waqf financing public expenditure be developed. Interviewees also agreed that federal government debt can be sustained through the means of this waqf application. Meanwhile, the quantitative part also showed that waqf financing public expenditure has an impact of reducing debt.